The epidemic of the multiresistant dermatophyte Trichophyton indotineae has reached China - Jia, Songgan; Long, Xuemei; Hu, Wei; Zhu, Jiali; Jiang, Yinhui; Ahmed, Sarah; de Hoog, G. Sybren; Liu, Weida; Jiang, Yanping (Frontiers in Immunology, 2023)
Due to its high degree of natural resistance to terbinafine in vitro and its tendency to spread globally from the Indian subcontinent, the emerging dermatophyte Trichophyton indotineae has become a major concern in dermatology. Herein, we present the first report of T. indotineae from mainland China. The transmission of the fungus to Guizhou Province in central China and eventual host susceptibilities were investigated. We studied 31 strains of the T. mentagrophytes complex from outpatient clinics of our hospital collected during the past 5 years. The set comprised four ITS genotypes, two of which were T. mentagrophytes type VIII, now known as Trichophyton indotineae; the earliest isolation in the Guiyang area appeared to date back to 2018. The isolate was derived from an Indian patient, while local Chinese patients had no dermatophytosis caused by this genotype. Reports from around the world indicated that almost all of the globally reported T. indotineae cases originated from the Indian subcontinent and surrounding countries without transmission among native populations, suggesting deviating local conditions or racial difference in immunity against this fungus.